Thermodynamic and Performance Assessment of an Innovative Solar-Assisted Tri-Generation System for Water Desalination, Air-Conditioning, and Power Generation - Fouda, A.; Elattar, H.; Rubaiee, S.; Bin Mahfouz, A. S.; Alharbi, A. M. (Engineering, Technology & Applied Science Research, 2022)
Abstract-An innovative tri-generation system powered by solar energy for water desalination, air-conditioning, and electrical power production is proposed and investigated numerically in this paper. The system is designed for small and medium-sized buildings in countries that are rich in solar energy but poor in fossil fuels and water resources. The devised system includes a solar system (evacuated tube collectors and thermal energy storage unit), an Organic Rankine Cycle (ORC), a Humidification and Dehumidification (HDH) water desalination system, and a Desiccant Cooling System (DCS). A detailed parametric study of the developed system is carried out for a wide range of operating conditions and design parameters on the system’s productivity and performance parameters. It is found that: (i) The proposed tri-generation system can deliver high electrical power, fresh water, space cooling capacity, and Energy Utilization Factor (EUF) of 104.5kW, 72.37kg/h, 25.48kW, and 0.2643 respectively. In comparison to the basic system, the EUFimp and ASC,sav parameters were enhanced having maximum values of 69.9% and 41.14% respectively. General numerical correlations derived from the numerical data can predict the system productivity and performance parameters within reasonable error.